Biomaterials and regenerative medicine - Ma, Peter X. (Cambridge : Cambridge University Press, 2014)
Written by world-leading experts, this book focusses on the role of biomaterials in stem cell research and regenerative medicine. Emphasising basic principles and methodology, it covers stem cell interactions, fabrication technologies, design principles, physical characterisation and biological evaluation, across a broad variety of systems and biomaterials. Topics include: stem cell biology, including embryonic stem cells, IPS, HSC and progenitor cells; modern scaffold structures, including biopolymer, bioceramic, micro- and nanofiber, ECM and biohydrogel; advanced fabrication technologies, including computer-aided tissue engineering and organ printing; cutting-edge drug delivery systems and gene therapy techniques; and medical applications spanning hard and soft tissues, the cardiovascular system and organ regeneration. With a contribution by Nobel laureate Shinya Yamanaka, this is a must-have reference for anyone in the field of biomaterials, stem cell biology and engineering, tissue engineering and regenerative medicine.
Contents note continued: 13.Computer-aided tissue engineering for modeling and fabrication of three-dimensional tissue scaffolds / Wei Sun -- pt. III Hydrogel scaffolds for regenerative medicine -- 14. Polysaccharide hydrogels for regenerative medicine applications / Jennifer H. Elisseeff -- 15. Functionalized poly(ethylene glycol) hydrogels for controlling stem cell fate / Chien-Chi Lin -- 16. Fumarate-based hydrogels in regenerative medicine applications / Antonios G. Mikos -- 17. Hydrogel scaffolds for regenerative medicine / Robert T. Tranquillo -- 18. Microfabricated gels for tissue engineering / Ali Khademhosseini -- 19.Organ printing / Thomas Boland -- pt. IV Biological factor delivery -- 20. Growth factor delivery on scaffolds / Peter X. Ma -- 21. Gene felivery for periodontal regeneration / William V. Giannobile -- 22. Endogenous stem/progenitor cell recruitment for tissue regeneration / Jeremy J. Mao -- 23. Affinity-based delivery systems / Horst A. von Recum.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Biomedical materials; Regenerative medicine; Stem cells -- Cytology